PENERAPAN GOOD GOVERNANCE DALAM PENGELOLAAN DANA DESA SELAMA PANDEMI COVID 19 - Iswahyudi Iswahyudi (JURNAL RISET AKUNTANSI TIRTAYASA, 2022)
This study applied qualitative descriptive method by evaluating the information presented in the SIDESKEL report and survey results. The basis of evaluation uses four criteria, namely transparent, accountable, participatory and orderly/budget discipline. The evaluation found that 15 villages in Plaosan sub-district, not all principles of Good Governance were applied in the Village Fund Management. The principles of Accountability, Participatory and Orderly/Budget Discipline have been met, but the Transparency principles have not been met. While the Accountability principle of the three criteria, there is still one criterion that has not been fulfilled, namely handling poverty that has not been perfect. This study shows the importance of implementing Good Governance in Village Fund Management which will provide a level of trust for the government. In addition, the application of Good Governance can make it easier to get funding sources from the government for the clarity of village programs. The Covid 19 pandemic has led to the renewal of legislation in the priority of using the Village Funds.of literature for that particular subject.